HIV prevention with Latinos theory, research, and practice - Organista, Kurt C. (New York ; Oxford : Oxford University Press, 2012)
This text, written by leading authorities on theory, research and practice in preventing HIV with diverse Latino populations and communities, responds to the diminishing returns of the behavioural model of HIV risk by deconstructing the many social ecological contexts of risk within the Latino experience.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Hispanic Americans -- Health and hygiene; AIDS (Disease) -- United States -- Prevention; Reproductive health -- Latin America; Reproductive health -- United States -- History